2013
DOI: 10.1590/s1983-40632013000200008
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de sementes de pimenta jalapenho em função da maturação e tempo de permanência nos frutos

Abstract: INTRODUÇÃOA pimenta jalapenho (Capsicum annuum L.) é originária da cidade de Jalapa, no México, e seu sabor medianamente picante possibilita sua utilização tanto para o consumo in natura quanto processado na forma de pó e molhos. Seu cultivo está difundido em muitas regiões do Brasil, pelo fato de ser excelente alternativa de renda para o produtor rural.As sementes de pimenta podem apresentar baixas taxas de germinação e dormência (Lakshmanan & Berke 1998), fato que, aliado ao desconhecimento do melhor estádio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
4
16
0
7
Order By: Relevance
“…During formation of P. dubium seeds, the difference in moisture content observed between the first two stages of maturity ( Figure 1A) may have been due to the immaturity of the seeds, since the variation observed, which reduced over time, is typical of orthodox seeds before physiological maturity (Nakada et al, 2011;Ricci et al, 2013). Tolerance to desiccation is acquired during development and allows reduction in moisture content to occur without damage to seeds (Bewley et al, 2013;Garnczarska et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During formation of P. dubium seeds, the difference in moisture content observed between the first two stages of maturity ( Figure 1A) may have been due to the immaturity of the seeds, since the variation observed, which reduced over time, is typical of orthodox seeds before physiological maturity (Nakada et al, 2011;Ricci et al, 2013). Tolerance to desiccation is acquired during development and allows reduction in moisture content to occur without damage to seeds (Bewley et al, 2013;Garnczarska et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic events that occur during maturation have the purpose of preparing the seed for its germination and, consequently, development of the seedling (Thomas, 1993;Kalemba and Pukacka, 2008). The increase in the concentration of proteins and other compounds during development and their maintenance after physiological maturity is important, especially when dealing with seeds that remain for a long period apart from the mother plant, as in serotinous species (Santini and Martorell, 2013). Maintenance of protein content is associated with low metabolic activity, as a result of reduction in moisture content during development and by the low activity of proteases, and by maintenance of the apparatus that impedes damage caused by reactive oxygen species and free radicals (Murthy et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research studies have reported the harvest season effects on species of the Solanaceae family, including tomato VIDIGAL et al, 2006), hot peppers (VIDIGAL et al, 2009a;QUEIROZ et al, 2011;VIDIGAL et al, 2011;ABUD et al, 2013;RICCI et al, 2013;PEREIRA et al, 2014), and eggplant (MARTINS et al, 2012). Vidigal et al (2009a) assessed peppers of the Amarela Comprida (C. annuum L.) variety harvested on 40, 50, 60, and 70 days after anthesis (DAA) and stored for 3, 6, 9, 12, and 15 days and found the best germination and vigor resulted in seeds from peppers harvested on 60 DAA that were not subjected to postharvest storage.…”
mentioning
confidence: 99%
“…A conservação eficiente das sementes, durante seu armazenamento, depende, dentre outros fatores, da sua qualidade inicial, a qual, por sua vez, está diretamente relacionada com a proximidade entre o momento em que as sementes atingem a maturidade fisiológica e o momento em que são colhidas (RICCI et al, 2013).…”
unclassified